2021
DOI: 10.1021/acsbiomaterials.0c01439
|View full text |Cite
|
Sign up to set email alerts
|

Design Considerations to Facilitate Clinical Radiological Evaluation of Implantable Biomedical Structures

Abstract: Clinical effectiveness of implantable medical devices would be improved with in situ monitoring to ensure device positioning, determine subsequent damage, measure biodegradation, and follow healing. While standard clinical imaging protocols are appropriate for diagnosing disease and injury, these protocols have not been vetted for imaging devices. This study investigated how radiologists use clinical imaging to detect the location and integrity of implanted devices and whether embedding nanoparticle contrast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…[ 63 ] Of particular note, 50 m m TaO x NPs were reported to provide sufficient signal/noise within tissue phantoms for clinical CT imaging. [ 64 ] On the other hand, another study reported in vivo micro‐CT imaging of 3D‐printed gelMA + Au scaffolds comprising 0.16 m m Au NPs, [ 38 ] but did not report X‐ray attenuation in Hounsfield units (HU) making interpretation difficult. Therefore, the relatively low concentration of Au NPs required for sufficient CT imaging contrast and monitoring degradation of the scaffolds in this in vitro study is encouraging but must be further investigated in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 63 ] Of particular note, 50 m m TaO x NPs were reported to provide sufficient signal/noise within tissue phantoms for clinical CT imaging. [ 64 ] On the other hand, another study reported in vivo micro‐CT imaging of 3D‐printed gelMA + Au scaffolds comprising 0.16 m m Au NPs, [ 38 ] but did not report X‐ray attenuation in Hounsfield units (HU) making interpretation difficult. Therefore, the relatively low concentration of Au NPs required for sufficient CT imaging contrast and monitoring degradation of the scaffolds in this in vitro study is encouraging but must be further investigated in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…MRI is able to provide sufficient contrast for imaging and monitoring degradation in hydrogel or polymeric scaffolds at lower NP concentrations, e.g., %0.4-10 mM (%0.01-0.2 wt%) Fe 3 O 4 NPs. [25][26][27]64] However, MRI is limited by low spatial and temporal resolution. [13] Optical imaging (e.g., fluorescence) has been more widely used to image and monitor scaffolds with even lower concentrations (μM) of fluorophores or NPs, [19][20][21][22][23][24] but is not suitable for deep tissue imaging due to the limited depth of light penetration(<1 cm).…”
Section: Study Implications and Limitationsmentioning
confidence: 99%
“…[4] However, for applications that require diagnosing implant damage, without concurrent interrogation of soft tissue status, the high clinical throughput, low-cost and favorable signal-to-noise ratio from surrounding tissue make CT beneficial for in situ monitoring. [3] To utilize CT for monitoring polymeric biomedical devices, radiopacity must be introduced.…”
Section: Introductionmentioning
confidence: 99%
“…To enable longitudinal non-invasive radiological monitoring of polymeric PNI devices, contrast must be introduced into the polymer matrix. The use of nanoparticulate contrast agents incorporated into polymeric devices has been shown to significantly increase radiologists’ ability to non-invasively identify implant location and damage, using computed tomography (CT) imaging and magnetic resonance imaging (MRI) [8,9]. While both techniques are widely used in the clinic, CT is a readily available and cost-effective imaging modality, that can generate high-resolution 3D images with no limitation on tissue depth [10].…”
Section: Introductionmentioning
confidence: 99%
“…While TaO x nanoparticle contrast agents have been demonstrated to significantly improve radiopacity of synthetic polymers [8], little is known about their interaction with nerve tissue or during the complex process of nerve regeneration. Repair of PNI is highly coordinated, relying on glial cells to first bridge the injury and then guide regenerating neurons across the site.…”
Section: Introductionmentioning
confidence: 99%